The Impact of Individualizing Sodium Bicarbonate Supplementation Strategies on World-Class Rowing Performance - Boegman, Susan; Stellingwerff, Trent; Shaw, Gregory; Clarke, Nick; Graham, Kenneth; Cross, Rebecca; Siegler, Jason C. (Frontiers in Nutrition, 2020)
Contemporary meta-analyses have generally demonstrated a positive effect of sodium bicarbonate (NaHCO3) supplementation on exercise performance. However, despite these claims, there is limited data on contrasting individualized and standardized timing of NaHCO3 ingestion prior to exercise to further enhance performance outcomes. Purpose: To determine whether NaHCO3 ingestion timing impacts 2000-m rowing time-trial (TT) performance in elite-level rowers (Senior National team including Olympic/World Championships level) adhering to their own individualized pre-race strategies (e.g. nutrition, warm-up, etc.). Methods: Twenty three (n = 23) rowers across two research centers (using the exact same methods/protocols) completed three trials: NaHCO3 loading profile at rest to determine the individual’s time-to-peak bicarbonate concentration [HCO3-], followed by two randomized 0.3 g·kgBM-1 NaHCO3 supplementation experimental trials conducted at different time points (consensus timing (CON): TT performed 60 min post-NaHCO3 ingestion; and individualized peak (IP): TT performed at the rower’s individual peak [HCO3-] determined from the profiling trial post-NaHCO3 ingestion). Results: There was a significant mean difference of +2.9 (± 0.4) mmol·L-1 HCO3- for IP vs. CON (95% CI 2.0 to 3.8 mmol·L-1); p = 0.02; d = 1.08) at pre warm-up, but not immediately prior to the TT (post warm-up). Performance times were significantly different between IP (367.0 ± 10.5 s) versus CON (369.0 ± 10.3 s); p = 0.007; d = 0.15). Conclusions: The present study demonstrated a small but significant performance effect of an individualized NaHCO3 ingestion strategy. Similarities after warm-up between pre-TT sHCO3- values (CON ~ + 5.5 mmol·L-1; IP ~ + 6 mmol·L-1), however, would suggest this effect was not a result of any meaningful differences in blood alkalinity.